Effects of colored lights on an individual's affective impressions in the observation process - Xie, Xing; Cai, Jun; Fang, Hai; Tang, Xiaoying; Yamanaka, Toshimasa (Frontiers in Psychology, 2022)
The lighting environment has an important influence on the psychological and physical aspects of a person. On certain occasions, reasonable lighting design can regulate people's emotions and improve their comfort feeling in the space. Besides, specific lighting can create a specific atmosphere according to space requirements. However, in the study of individual’s affective impressions, there is still some uncertainty about how colored lights affect individual’s mood and impressions towards visual objects. This research improves the understanding of the emotional impact of colored light in space. To better understand the lighting environment in observation process, the project studied the effects of four groups of lights (green, blue, red, and yellow) on the participants' mood and impressions. Participants watched two sets of visual images under four different lighting conditions, and feedback their emotions and evaluations through Multiple Mood States Scale, Two-Dimensional Mood Scale, and Semantic Differential Scale. The results show that different colors of light have a significant effect on mood, and red light can arouse the emotion changes of calm, irritated, relaxed, nervous, stability, and pleasure. At the same time, different colors of light have a certain relevance to participants’ impressions and also provides further research value for the design of the colored light environment in individual’s affective impressions. Therefore, this study discusses the feasibility of colored lights as a display method, which has potential application prospects for constructing different space atmospheres.